P-gp/ABCB1 exerts differential impacts on brain and fetal exposure to norbuprenorphine. (May 2017) - Liao, Michael Z.; Gao, Chunying; Shireman, Laura M.; Phillips, Brian; Risler, Linda J.; Neradugomma, Naveen K.; Choudhari, Prachi; Prasad, Bhagwat; Shen, Danny D.; Mao, Qingcheng
Graphical abstract: Abstract: Norbuprenorphine is the major active metabolite of buprenorphine which is commonly used to treat opiate addiction during pregnancy. Norbuprenorphine produces marked respiratory depression and was 10 times more potent than buprenorphine. Therefore, it is important to understand the mechanism that controls fetal exposure to norbuprenorphine, as exposure to this compound may pose a significant risk to the developing fetus. P-gp/ABCB1 and BCRP/ABCG2 are two major efflux transporters regulating tissue distribution of drugs. Previous studies have shown that norbuprenorphine, but not buprenorphine, is a P-gp substrate. In this study, we systematically examined and compared the roles of P-gp and BCRP in determining maternal brain and fetal distribution of norbuprenorphine using transporter knockout mouse models. We administered 1 mg/kg norbuprenorphine by retro-orbital injection to pregnant FVB wild-type, Abcb1a −/− / 1b −/−, and Abcb1a −/− / 1b −/− / Abcg2 −/− mice on gestation day 15. The fetal AUC of norbuprenorphine was ∼64% of the maternal plasma AUC in wild-type mice, suggesting substantial fetal exposure to norbuprenorphine. The maternal plasma AUCs of norbuprenorphine in Abcb1a −/− / 1b −/− and Abcb1a −/− / 1b −/− / Abcg2 −/− mice were ∼2 times greater than that in wild-type mice. Fetal AUCs in Abcb1a −/− / 1b −/− and Abcb1a −/− / 1b −/− / Abcg2 −/− mice were also increased compared to wild-type mice; however, the fetal-to-maternal plasma AUC ratio remained relatively unchanged by the knockout of Abcb1a/1b or Abcb1a/1b/Abcg2 . In contrast, the maternal brain-to-maternal plasma AUC ratio in Abcb1a −/− / 1b −/− or Abcb1a −/− / 1b −/− / Abcg2 −/− mice was increased ∼30-fold compared to wild-type mice. Protein quantification by LC–MS/MS proteomics revealed significantly higher amounts of P-gp protein in the wild-type mice brain than that in the placenta. These results indicate that fetal exposure to norbuprenorphine is substantial and that P-gp has a minor impact on fetal exposure to norbuprenorphine, but plays a significant role in restricting its brain distribution. The differential impacts of P-gp on norbuprenorphine distribution into the brain and fetus are likely, at least in part, due to the differences in amounts of P-gp protein expressed in the blood-brain and blood-placental barriers. BCRP is not as important as P-gp in determining both the systemic and tissue exposure to norbuprenorphine. Finally, fetal AUCs of the metabolite norbuprenorphine-β-d -glucuronide were 3–7 times greater than maternal plasma AUCs, while the maternal brain AUCs were <50% of maternal plasma AUCs, suggesting that a reversible pool of conjugated metabolite in the fetus may contribute to the high fetal exposure to norbuprenorphine.